Cationic disordered lithium-rich rock salt positive electrode material and preparation method thereof, positive electrode sheet and lithium battery

The surface modification of the cationic disordered lithium-rich rock salt structure material through aluminum salt and oxalate is carried out to form a gradient lithium-poor layer, which solves the problem of oxygen molecules overflow during the charging and discharging of the material, and significantly improves the cyclic stability of the material and Overall performance of lithium batteries.

CN116072847BActive Publication Date: 2025-02-21SUZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310105373.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-13
Publication Date
2025-02-21
Estimated Expiration
2043-02-13

AI Technical Summary

Technical Problem

The cationic disordered lithium-rich rock salt structure material oxidation and reduction of oxygen during charging and discharging causes the overflow of surface oxygen molecules, causing irreversible loss of specific capacity and structural damage, affecting the cyclic stability of the material.

Method used

The surface modification of the cationic disordered lithium-rich rock salt structure material is used to form a gradient lithium-poor layer. It is cleaned by high-temperature calcination and sodium hydroxide to form a uniform and consistent lithiated surface layer to inhibit the molecular oxygen of the surface layer. overflow.

Benefits of technology

It effectively improves the circulation stability of the material, significantly enhances the structural stability, and improves the overall performance of lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure HDA0004074568020000011
    Figure HDA0004074568020000011
  • Figure HDA0004074568020000012
    Figure HDA0004074568020000012
Patent Text Reader

Abstract

The present application relates to the field of lithium batteries, and discloses a cationic disordered lithium-rich rock salt positive electrode material and a preparation method thereof, as well as a positive electrode sheet and a lithium battery. The positive electrode material described in the present application includes a core layer material and an epitaxial coherent surface layer material; the core layer material is a cationic disordered lithium-rich rock salt structure material, and the chemical formula is Li a Mn 0.4 M b O2, the M represents a transition metal, 1.1≤a≤1.3, b=(2.8‑a) / m, m is the valence of the transition metal M; the epitaxial coherent surface material covers the core material, and the chemical formula is Li a‑ 2x Mn 0.4 M b O 2‑x , 0<x<0.1. The cathode material described in the present application uses aluminum salt to modify the surface of the cationic disordered lithium-rich rock salt structure material, and forms a gradient lithium-poor layer in situ on its surface, which effectively inhibits the generation and overflow of surface molecular oxygen and significantly enhances the stability of the material structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of lithium batteries, and specifically to a cationic disordered lithium-rich rock salt positive electrode material and a preparation method thereof, as well as a positive electrode sheet and a lithium battery. Background Art

[0002] With the rapid development of new energy electric vehicles, grid energy storage and portable electronic devices, the requirements for high performance and low cost of lithium-ion batteries are getting higher and higher. Existing commercial lithium-ion battery cathode materials such as lithium cobalt oxide, lithium iron phosphate and ternary cathode materials are increasingly difficult to meet people's requirements in terms of performance and cost, and there is an urgent need to study new battery materials. Cationic disordered lithium-rich rock salt structure materials are considered to be very promising next-generation lithium battery cathode materials due to their ultra-high specific capacity and energy density as well as the rich reserves of elements in the earth's crust.

[0003] The reason why cationic disordered lithium-rich rock salt structural materials have ultra-high specific capacity is that in addition to transition metals, the redox of oxygen during the charge and discharge process also provides additional capacity. However, the redox of oxygen during the charge and discharge process will form oxygen molecules, and the oxygen molecules formed on the surface of the material are easy to overflow in the form of oxygen, which on the one hand leads to irreversible loss of specific capacity, and on the other hand causes structural damage, thus affecting the cyclic stability of the material. This problem of cationic disordered lithium-rich rock salt structural materials seriously affects its commercial application prospects.

[0004] The method reported so far to improve the cycle stability of disordered lithium-rich materials is mainly to coat their surface with carbon materials or oxides. However, surface coating will reduce the energy density of the composite material on the one hand, and the uneven coating also makes its effect on the cycle stability of disordered lithium-rich materials very limited on the other hand. Therefore, it is necessary to develop a new surface treatment method to inhibit the overflow of molecular oxygen on the surface of the material and improve the cycle stability of the material. Summary of the invention

[0005] In view of this, the purpose of the present application is to provide a cationic disordered lithium-rich rock salt positive electrode material and a preparation method thereof, so that the positive electrode material can improve the overflow phenomenon of molecular oxygen on the surface of the cationic disordered lithium-rich rock salt structure material, thereby improving its cycle stability performance;

[0006] Another object of the present application is to provide a positive electrode sheet and a lithium battery based on the above-mentioned positive electrode material.

[0007] In order to solve the above technical problems / achieve the above purposes or at least partially solve the above technical problems / achieve the above purposes, as a first aspect of the present application, a cationic disordered lithium-rich rock salt positive electrode material is provided, including a core layer material and an epitaxial coherent surface layer material; the core layer material is a cationic disordered lithium-rich rock salt structure material, and the chemical formula is Lia Mn 0.4 M b O2, the M represents a transition metal, 1.1≤a≤1.3, b= (2.8-a) / m, m is the valence of the transition metal M; the epitaxial coherent surface material covers the core material, and the chemical formula is Li a-2x Mn 0.4 M b O 2-x , 0<x<0.1.

[0008] Optionally, the transition metal includes one or more of Nb, Zr and Ti.

[0009] Optionally, the chemical formula of the cation disordered lithium-rich rock salt structure material is Li 1.2 Ti 0.4 Mn 0.4 O2、Li 1.2 Mn 0.4 Zr 0.4 O2 or Li 1.3 Mn 0.4 Nb 0.3 O2.

[0010] As a second aspect of the present application, a method for preparing the positive electrode material is provided, comprising:

[0011] Aluminum salt, oxalate and cationic disordered lithium-rich rock salt structure material are dispersed in a solvent to form a mixed solution;

[0012] An alkaline pH regulator is added to the mixed solution to react, forming a lithium-poor epitaxial coherent surface material on the surface of the cationic disordered lithium-rich rock salt structure material, which is then calcined. After calcination, sodium hydroxide is used to remove surface LiAlO2 and aluminum oxide to obtain the positive electrode material.

[0013] Optionally, the oxalate includes ammonium oxalate and / or sodium oxalate, and the aluminum salt includes one or more of aluminum nitrate, aluminum sulfate, and aluminum chloride.

[0014] Optionally, the alkaline pH adjuster includes aqueous ammonia.

[0015] Optionally, the calcination temperature is 600-1200°C.

[0016] As the third aspect of the present application, based on the excellent performance of the positive electrode material described in the present application, its application in the preparation of positive electrode sheets or lithium batteries is proposed.

[0017] As a fourth aspect of the present application, a positive electrode plate is provided, comprising a current collector, a conductive agent, a binder and the positive electrode material described in the present application.

[0018] As a fifth aspect of the present application, a lithium battery is provided, comprising a negative electrode plate, an electrolyte, a separator and the positive electrode plate described in the present application.

[0019] Compared with the existing cation disordered lithium-rich rock salt structure materials, the positive electrode material described in the present application has at least the following beneficial effects:

[0020] (1) Aluminum salts are used to modify the surface of cationic disordered lithium-rich rock salt structure materials, forming a gradient lithium-poor layer in situ on their surface, which effectively inhibits the generation and overflow of surface molecular oxygen and significantly enhances the structural stability of the material;

[0021] (2) In the preparation of the positive electrode material of the present application, the oxalate additive provided can quickly and effectively form aluminum hydroxide, which is evenly coated on the surface of the cationic disordered lithium-rich rock salt structure material, thereby obtaining a uniform surface gradient lithium-poor layer;

[0022] (3) The surface modification and performance optimization method of the cationic disordered lithium-rich rock salt structure material provided in this application is simple and easy to operate, with mild reaction conditions, which effectively improves the cyclic stability of the material and has strong applicability. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Shown are the defects of the cation disordered lithium-rich rock salt structure material and its surface modification effect;

[0024] Figure 2 The Li in Example 1 is shown 1.2 Ti 0.4 Mn 0.4 SEM and EDS images of O2 after modification by aluminum salt treatment (without NaOH cleaning);

[0025] Figure 3 The Li in Example 1 is shown 1.2 Ti 0.4 Mn 0.4 SEM image of O2 after modification by aluminum salt and cleaning with NaOH;

[0026] Figure 4 The Li in Example 1 is shown 1.2 Ti 0.4 Mn 0.4 XRD spectra before and after O2 modification; the black line (bottom) represents the result before modification, the blue line (middle) represents the result after aluminum salt treatment modification (without NaOH cleaning), and the red line (top) represents the result after NaOH cleaning. DETAILED DESCRIPTION

[0027] The present application discloses a cationic disordered lithium-rich rock salt positive electrode material and a preparation method thereof, as well as a positive electrode sheet and a lithium battery. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all deemed to be included in this application. The products, applications and methods of this application have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods described herein without departing from the content, spirit and scope of the present invention to realize and apply the technology of the present invention.

[0028] At present, the oxidation and reduction of oxygen in the charging and discharging process of the cationic disordered lithium-rich rock salt structure material will form oxygen molecules. The oxygen molecules formed on the surface of the material are easy to overflow in the form of oxygen, causing its structure to collapse, causing a series of problems in lithium batteries. In view of this defect, in the first aspect of the present application, a cationic disordered lithium-rich rock salt positive electrode material is provided, including a core layer material and an epitaxial coherent surface layer material; the core layer material is a cationic disordered lithium-rich rock salt structure material, and the chemical formula is Li a Mn 0.4 M b O2, wherein M represents a transition metal, 1.1≤a≤1.3, b= (2.8-a) / m, and m is the valence of the transition metal M; the epitaxial coherent surface material covers the core material, which is a lithium-poor surface layer produced under the combined action of aluminum salt, oxalate, cationic disordered lithium-rich rock salt and high temperature. After ICP-AES and EELS determination, the lithium-poor degree is gradually deepened from the inside to the outside, and the chemical formula is Li a-2x Mn 0.4 M b O 2-x , 0<x<0.1, see the schematic diagram Figure 1 In the coated state of the lithium-poor surface layer, O2 is difficult to overflow, while lithium ions can pass freely, thereby improving the cyclic stability of the material.

[0029] In certain embodiments of the present application, the particle size of the positive electrode material is 5-10 microns, and the thickness of the epitaxial coherent surface material is 10-20 nanometers.

[0030] In some embodiments of the present application, the transition metal includes one or more of Nb, Zr and Ti; in some other embodiments of the present application, the cationic disordered lithium-rich rock salt structure material has a chemical formula of Li 1.2 Ti 0.4 Mn 0.4 O2、Li 1.2 Mn 0.4 Zr 0.4 O2 or Li 1.3 Mn 0.4 Nb 0.3O2.

[0031] In a second aspect of the present application, a method for preparing the positive electrode material is provided, comprising:

[0032] Aluminum salt, oxalate and cationic disordered lithium-rich rock salt structure material are dispersed in a solvent to form a mixed solution;

[0033] An alkaline pH regulator is added to the mixed solution to react, forming a lithium-poor epitaxial coherent surface material on the surface of the cationic disordered lithium-rich rock salt structure material, which is then calcined. After calcination, sodium hydroxide is used to remove surface LiAlO2 and aluminum oxide to obtain the positive electrode material.

[0034] During the preparation process, under the combined action of oxalate and ammonia, aluminum is uniformly coated in the cationic disordered lithium-rich rock salt structure material Li in the form of hydroxide. a Mn 0.4 M b O2 surface, aluminum hydroxide and Li at high temperature a Mn 0.4 M b O2 reacts as follows:

[0035] Li a Mn 0.4 M b O2+2xAl(OH)3→Li a-2x Mn 0.4 M b O 2-x + 2xLiAlO2+3xH2O

[0036] By Li 1.2 Ti 0.4 Mn 0.4 Take O2 as an example, the reaction equation is as follows:

[0037] Li 1.2 Mn 0.4 Ti 0.4 O2+2xAl(OH)3→Li 1.2-2x Mn 0.4 Ti 0.4 O 2-x + 2xLiAlO2+3xH2O

[0038] Li a Mn 0.4 M bPart of the Li2O on the surface of O2 is released to form a lithium-poor surface layer with a certain concentration gradient, and the released Li2O combines with aluminum compounds to form LiAlO2. LiAlO2 subsequently reacts and dissolves with NaOH solution, and finally a surface gradient lithium-poor modified positive electrode material is obtained. Its lithium-poor surface layer can effectively inhibit the redox of surface oxygen and prevent the irreversible overflow of surface oxygen, thereby greatly improving the cycle stability of the disordered lithium-rich material.

[0039] In certain embodiments of the present application, the molar ratio of the aluminum salt, oxalate and cationic disordered lithium-rich rock salt structure material is 1:1-5:10-50; in other embodiments of the present application, the molar ratio of the aluminum salt, oxalate and cationic disordered lithium-rich rock salt structure material is 1:1.7:26.4, 1:2.4:13.2, 1:2.8:42.8, 1:3.2:16.5 or 1:2.6:13.2.

[0040] In certain embodiments of the present application, the oxalate includes ammonium oxalate and / or sodium oxalate, and the aluminum salt includes one or more of aluminum nitrate, aluminum sulfate, and aluminum chloride.

[0041] In certain embodiments of the present application, the alkaline pH regulator includes ammonia water; in other embodiments of the present application, the concentration of the alkaline pH regulator is 0.2%-1% (V / V), for example, 0.2%, 0.5% or 1%; in other embodiments of the present application, the alkaline pH regulator is added for a time of 2-6 hours to make the surface coating more uniform; in other embodiments of the present application, the molar ratio of the alkaline pH regulator to the aluminum salt is 5-40:1, for example, 30.5:1, 15.2:1, 24.4:1, 19:1, 12.2:1.

[0042] In certain embodiments of the present application, the calcination is carried out in a protective gas atmosphere, such as nitrogen or an inert gas (such as argon); the calcination temperature is 600-1200°C, such as 600°C, 800°C, 1000°C or 1200°C; in other embodiments of the present application, the calcination time is 2-6h, such as 2h, 3h, 4h, 5h or 6h.

[0043] In certain embodiments of the present application, the calcined material is added to a NaOH solution and continuously stirred to remove surface LiAlO2 and aluminum oxide. If necessary, the solution can be filtered and the NaOH solution of the same concentration can be added again and stirred, which can be repeated 2-3 times; in other embodiments of the present application, in order to further improve the removal efficiency, auxiliary heating can be performed, such as continuous stirring in an oil bath at 80°C; in other embodiments of the present application, the concentration of NaOH solution is 0.5-2mol / L, such as 0.5mol / L, 1mol / L or 2mol / L; the amount of NaOH can be excessive, and its molar ratio to aluminum salt is generally ≥10:1.

[0044] In the third aspect of the present application, compared with the conventional solid phase carbon coating scheme, the scheme without adding oxalate and the scheme using aluminum acetate, the capacity retention rate of the lithium battery composed of the positive electrode material of the present application is improved by more than 15% after 100 cycles. Based on this excellent performance, its application in the preparation of positive electrode sheets or lithium batteries is proposed.

[0045] In a fourth aspect of the present application, a positive electrode plate is provided, comprising a current collector, a conductive agent, a binder and the positive electrode material described in the present application.

[0046] In certain embodiments of the present application, the positive electrode plate includes a current collector and a slurry coated on the current collector; wherein the current collector can be selected from a metal foil with good conductivity, such as aluminum foil; the slurry includes the positive electrode material described in the present application, as well as a binder and a conductive agent, the binder, the conductive agent and their amounts are selected according to conventional methods, and the present application does not impose specific restrictions, for example, the binder is polyvinylidene fluoride (PVDF), styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC), etc., the conductive agent is conductive carbon black (SP), acetylene black, etc., the solvent is N-methylpyrrolidone (NMP), deionized water, etc., and the positive electrode material: conductive agent: binder = 7:2:1.

[0047] In a fifth aspect of the present application, a lithium battery is provided, comprising a negative electrode plate, an electrolyte, a separator and the positive electrode plate described in the present application.

[0048] In certain embodiments of the present application, the lithium-ion battery is a full battery, a soft-pack battery, a Swagelok battery, or a button battery.

[0049] In certain embodiments of the present application, the negative electrode plate is a metal lithium plate; the diaphragm is a glass fiber diaphragm; the electrolyte is a 1.0-1.5 mol / L LiPF6 solution, for example, a LiPF6 electrolyte with ethylene carbonate (EC) and dimethyl carbonate (DMC) as solvent in a volume ratio of 1:1.

[0050] In each group of comparative experiments provided in this application, unless otherwise specified, other experimental conditions, materials, etc. are kept consistent except for the differences indicated in each group, so as to provide comparability. In addition, all materials used in this application can be purchased through commercial channels.

[0051] The cationic disordered lithium-rich rock salt structure material described in the present application can be prepared according to the reported preparation process, generally, each raw material is weighed and ball-milled according to the chemical formula, and then roasted to obtain it; Take the preparation of Li 1.2 Ti 0.4 Mn 0.4 O2 Description: Mn2O3, TiO2 and 10% excess Li2CO3 are weighed according to the stoichiometric ratio, ball milled for 8 hours, and calcined at 900℃ for 8 hours.

[0052] The following is a further description of a cationic disordered lithium-rich rock salt positive electrode material and a preparation method thereof, as well as a positive electrode plate and a lithium battery provided in this application.

[0053] Embodiment 1:

[0054] (1) Mix 100 mg aluminum nitrate, 100 mg ammonium oxalate and 1 g Li 1.2 Ti 0.4 Mn 0.4 O2 (the molar ratio of the three was 1:1.7:26.4) was dispersed in 500 ml of deionized water, ultrasonicated for 1 h and then stirred for 2 h.

[0055] (2) Prepare 100 ml of 0.5% (V / V) ammonia solution (ammonia to aluminum salt molar ratio is 30.5:1) and slowly add it dropwise to the solution in step 1. Stir the solution continuously during the addition and control the addition time to 4 h.

[0056] (3) The solution obtained in step 2 was filtered, placed in a vacuum drying oven at 80°C for 12 h, calcined at 1000°C for 2 h in an argon atmosphere, and then cooled naturally. The SEM and EDS images are shown in Figure 2 .

[0057] (4) Add the material treated at high temperature in step 3 to an excess of NaOH aqueous solution, place the solution in an 80°C oil bath and stir for 12 hours. Then filter the solution, add it to a NaOH solution of the same concentration and continue heating and stirring, then filter it, repeat 2-3 times. Finally, a cationic disordered lithium-rich rock salt cathode material with a surface poor lithium modification is obtained, as shown in the SEM image. Figure 3 .

[0058] Figure 2 The EDS results show that aluminum salts have a strong affinity for Li 1.2 Ti 0.4 Mn 0.4 O2 modification is mainly concentrated on the particle surface; in addition, for Li1.2 Ti 0.4 Mn 0.4 XRD detection was performed before and after O2 modification. Figure 4 The results showed that after aluminum salt modification (before sodium hydroxide cleaning), Li 1.2 Ti 0.4 Mn 0.4 A lithium-poor layer is formed on the surface of O2, and Li2O reacts to form LiAlO2. After washing with sodium hydroxide, LiAlO2 is removed, which can prevent the occurrence of side reactions when used in lithium batteries and improve the specific capacity at the same time.

[0059] Embodiment 2:

[0060] (1) Mix 200 mg aluminum nitrate, 300 mg sodium oxalate and 1 g Li 1.2 Ti 0.4 Mn 0.4 O2 (the molar ratio of the three was 1:2.4:13.2) was dispersed in 500 ml of deionized water, ultrasonicated for 4 h and then stirred for 2 h.

[0061] (2) Prepare 50 ml of 1% (V / V) ammonia solution (the molar ratio of ammonia solution to aluminum salt is 15.2:1), and slowly add it dropwise to the solution in step 1. Stir the solution continuously during the addition, and control the addition time to 6 h.

[0062] (3) The solution obtained in step 2 was filtered and dried in a vacuum drying oven at 80°C for 12 hours. The solution was calcined at 1200°C for 2 hours in an argon atmosphere and then cooled naturally.

[0063] (4) Add the material treated with high temperature in step 3 to 1000 ml of 1 mol / L NaOH aqueous solution, place the solution in an 80°C oil bath and stir for 12 hours. Then filter the solution, add it to the same concentration of NaOH solution again, continue heating and stirring, and then filter it, repeat 2-3 times. Finally, a cationic disordered lithium-rich rock salt positive electrode material with surface lithium-deficient modification is obtained.

[0064] Embodiment 3:

[0065] (1) Mix 100 mg of aluminum sulfate, 100 mg of ammonium oxalate and 1 g of Li 1.2 Ti 0.4 Mn 0.4 O2 (the molar ratio of the three was 1:2.8:42.8) was dispersed in 500 ml of deionized water, ultrasonicated for 1 h and then stirred for 2 h.

[0066] (2) Prepare 50 ml of 0.5% (V / V) ammonia solution (the molar ratio of ammonia solution to aluminum salt is 24.4:1), and slowly add it dropwise to the solution in step 1. Stir the solution continuously during the addition, and control the addition time to 4 h.

[0067] (3) The solution obtained in step 2 was filtered and dried in a vacuum drying oven at 80°C for 12 h. The solution was calcined at 800°C for 2 h in an argon atmosphere and then cooled naturally.

[0068] (4) Add the material treated at high temperature in step 3 to an excess of NaOH aqueous solution, place the solution in an 80°C oil bath and stir for 12 hours. Then filter the solution, add it to a NaOH solution of the same concentration and continue heating and stirring, then filter it, and repeat 2-3 times. Finally, a cationic disordered lithium-rich rock salt positive electrode material with surface lithium-deficient modification is obtained.

[0069] Embodiment 4:

[0070] (1) Mix 100 mg aluminum chloride, 300 mg ammonium oxalate and 1 g Li 1.2 Ti 0.4 Mn 0.4 O2 (the molar ratio of the three was 1:3.2:16.5) was dispersed in 500 ml of deionized water, ultrasonicated for 1 h and then stirred for 2 h.

[0071] (2) Prepare 50 ml of 1% (V / V) ammonia solution (the molar ratio of ammonia solution to aluminum salt is 19:1), and slowly add it dropwise to the solution in step 1. Stir the solution continuously during the addition, and control the addition time to 4 h.

[0072] (3) The solution obtained in step 2 was filtered and dried in a vacuum drying oven at 80°C for 12 h. The solution was calcined at 600°C for 2 h in an argon atmosphere and then cooled naturally.

[0073] (4) Add the material treated at high temperature in step 3 to an excess of NaOH aqueous solution, place the solution in an 80°C oil bath and stir for 12 hours. Then filter the solution, add it to a NaOH solution of the same concentration and continue heating and stirring, then filter it, and repeat 2-3 times. Finally, a cationic disordered lithium-rich rock salt positive electrode material with surface lithium-deficient modification is obtained.

[0074] Embodiment 5:

[0075] (1) Mix 200 mg aluminum nitrate, 300 mg ammonium oxalate and 1 g Li 1.2 Ti 0.4 Mn 0.4 O2 (the molar ratio of the three was 1:2.6:13.2) was dispersed in 500 ml of deionized water, ultrasonicated for 1 h and then stirred for 2 h.

[0076] (2) Prepare 200 ml of 0.2% (V / V) ammonia solution (molar ratio of ammonia solution to aluminum salt is 12.2:1), and slowly add it dropwise to the solution in step 1. Stir the solution continuously during the addition, and control the addition time to 6 h.

[0077] (3) The solution obtained in step 2 was filtered and dried in a vacuum drying oven at 80°C for 12 hours. The solution was calcined at 1000°C for 4 hours in an argon atmosphere and then cooled naturally.

[0078] (4) Add the material treated at high temperature in step 3 to an excess of NaOH aqueous solution, place the solution in an 80°C oil bath and stir for 12 hours. Then filter the solution, add it to a NaOH solution of the same concentration and continue heating and stirring, then filter it, and repeat 2-3 times. Finally, a cationic disordered lithium-rich rock salt positive electrode material with surface lithium-deficient modification is obtained.

[0079] Comparative Example 1:

[0080] Conventional solid phase carbon coating: same as Li in Example 1 1.2 Ti 0.4 Mn 0.4 O2 and acetylene black were added into a ball mill at a mass ratio of 9:1. The ball milling speed was 300 rpm and the ball milling time was 4 h. Finally, a disordered lithium-rich material with a carbon coating of 10 wt% was obtained.

[0081] Comparative Example 2:

[0082] The control positive electrode material was prepared by referring to Example 1, but without adding ammonium oxalate and keeping other conditions the same.

[0083] Comparative Example 3:

[0084] The control positive electrode material was prepared by referring to Example 1, except that the aluminum salt was changed to aluminum acetate (the amount of the substance remained the same as that of aluminum nitrate) and the other conditions were the same.

[0085] Experimental example:

[0086] The materials prepared in Examples 1-5 and Comparative Examples 1-3 were used as positive electrode active materials, and acetylene black (conductive agent) and PVDF (binder) were weighed in a mass ratio of 7:2:1, ground in a mortar for a period of time, and then N-methylpyrrolidone (NMP) was added after uniform mixing, and grinding was continued to obtain a uniform black viscous slurry. The prepared slurry was placed on aluminum foil and coated into a film of uniform thickness with a scraper. Metal lithium was used as the counter electrode, glass fiber membrane was used as the diaphragm, and 1 mol / L LiPF6 / EC:DMC (1:1) was used as the electrolyte. CR2032 button batteries were assembled in an argon atmosphere glove box.

[0087] The first cycle specific capacity and capacity after 100 cycles of the materials of Examples 1-5 and Comparative Examples 1-3 at a rate of 20 mA / g are shown in Table 1 below:

[0088] Table 1 Comparison of the first cycle specific capacity and capacity after 100 cycles of different samples

[0089]

[0090] It can be clearly seen from Table 1 that the capacity retention rate of Examples 1-5 of the present application after 100 cycles is significantly higher than that of Comparative Examples 1-3, which on the one hand shows that the positive electrode material of the present application is superior to the conventional carbon coating scheme, and on the other hand shows the role of oxalate and aluminum salt in the preparation process of the present application.

[0091] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A cation disordered lithium-rich rock salt positive electrode material, characterized in that: It includes a core layer material and an epitaxial coherent surface layer material; the core layer material is a cationic disordered lithium-rich rock salt structure material with a chemical formula of Li a Mn 0.4 M b O2, the M represents a transition metal, 1.1≤a≤1.3, b= (2.8-a) / m, m is the valence of the transition metal M; the epitaxial coherent surface material covers the core material, and the chemical formula is Li a-2x Mn 0.4 M b O 2-x , 0<x<0.1; The positive electrode material is prepared according to the following preparation method: Aluminum salt, oxalate and cationic disordered lithium-rich rock salt structure material are dispersed in a solvent to form a mixed solution; An alkaline pH regulator is added to the mixed solution to react, forming a lithium-poor epitaxial coherent surface material on the surface of the cationic disordered lithium-rich rock salt structure material, which is then calcined. After calcination, sodium hydroxide is used to remove surface LiAlO2 and aluminum oxide to obtain the positive electrode material.

2. The positive electrode material according to claim 1, characterized in that The transition metal includes one or more of Nb, Zr and Ti.

3. The positive electrode material according to claim 1, characterized in that The chemical formula of the cation disordered lithium-rich rock salt structure material is Li 1.2 Ti 0.4 Mn 0.4 O2、Li 1.2 Mn 0.4 Zr 0.4 O2 or Li 1.3 Mn 0.4 Nb 0.3 O2.

4. The positive electrode material according to claim 1, characterized in that The oxalate includes ammonium oxalate and / or sodium oxalate, and the aluminum salt includes one or more of aluminum nitrate, aluminum sulfate, and aluminum chloride.

5. The positive electrode material according to claim 1, characterized in that The alkaline pH adjuster includes aqueous ammonia.

6. The positive electrode material according to claim 1, characterized in that The calcination temperature is 600-1200°C.

7. Use of the positive electrode material according to any one of claims 1 to 6 in the preparation of positive electrode sheets or lithium batteries.

8. A positive electrode sheet, characterized in that: The invention comprises a current collector, a conductive agent, a binder and the positive electrode material according to any one of claims 1 to 3.

9. A lithium battery, characterized in that: It comprises a negative electrode sheet, an electrolyte, a separator and the positive electrode sheet as claimed in claim 8.

Citation Information

Patent Citations

  • Lithium-rich nickel-titanium-molybdenum oxide positive electrode material, positive electrode pole piece and preparation method thereof, and lithium battery

    CN110165165A

  • Method for preparing cationic unordered rock salt structure anode material through high-valent-state transition metal ion replacement combination strategies

    CN110372039A